Understanding Reusability as a Key Factor for Open Education: A Review - Chiappe, Andres; Arias, Vivian (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2015)
This article describes both the process and the results of an extensive literature review on reusability as one of the key factors for the creation of open content in the context of open and distance learning. Qualitative analysis of texts was made from 1992 to early 2014 in order to identify meanings associated with reusability and its evolution over time. Results show that reusability is not a univocal concept and its meaning has evolved from its early years, especially focusing over the last decade on adaptation processes. Furthermore, the review indicates that reusability has traveled through a complex path from a technological to an educational context and the ideas related to it, in each case, projected different practical implications. A more profound understanding of such ideas is critical to face institutional approaches to create and reuse open educational resources as well as the design and implementation of open educational practices.